Pemanfaatan Framework Codeigniter dalam Pengembangan Sistem Informasi Pendataan Laporan Kerja Praktek Mahasiswa Program Studi Teknik Informatika Unsoed - Lasmedi Aufan (JUITA : Jurnal Informatika, 2010)
The development of Internet and Web developing so quickly, giving rise to a new branch of Science (engineering Web) Web engineering technology.Web Engineering is a new branch of science which includes the study of evolution or the web using the framework, application engineering process which is why web development easier and faster. Deepening knowledgeof the author about using CodeIgniter framework, the authors developed a collecting data report on practical work study program Unsoed Informatics student information system